For the love of sun and wind? Proximity to renewable energy facilities and support for renewable power across time and space in the United States. (March 2021) - Mayer, Adam; Hazboun, Shawn Olson; Howe, Peter D.
Abstract: The relationship between proximity to energy development and public support is inconsistent. Research indicates that proximity to fossil fuels is associated with higher support for that fuel source, yet these relationships vary across time and space and have rarely been studied for renewable energy. We use two waves of a U.S. national survey and novel propensity-score-based pseudo panel methods to analyze how proximity to renewable energy influences public support for its expanded use. Results indicate proximity to renewable energy development does not predict support, and panel regression results suggest that growth in local renewable energy has not altered support for renewables. Rather, political factors and climate change risk perceptions are most influential. Unlike fossil fuel industries, proximity to renewable energy does not predict support for using these technologies. Although more research is needed, we suggest that renewables, as of 2016, lack the cultural and social significance of fossil fuels.